Experiences of patients and service providers with out-patient rehabilitation services in a rehabilitation centre in the Western Cape Province - Anne Kumurenzi; Charlyn Goliath; Gubela Mji; Nondwe Mlenzana; Conran Joseph; Sue Stathum; Anthea Rhoda (African Journal of Disability, 2015)
Background: Rehabilitation is important for persons with disabilities as it contributes to their sense of autonomy, self-worth and social participation, and improves their quality of life. Improving the quality of rehabilitation services requires the dialogue of patients’ perceptions with those of service providers, in order to recommend informed reform. Objective: The objective was to explore the experiences of persons with physical disabilities and service providers, regarding the multi-disciplinary rehabilitation services provided at a community-based out-patient rehabilitation centre.